Development and Modelling of Three Phase Inverter for Harmonic Improvement using Sinusoidal Pulse Width Modulation (SPWM) Control Technique - Buswig, Yonis.M.Yonis; Al-Khalid, Bin Hj Othman; Norhuzaimin, Bin Julai (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2019)
This paper describes the design of a 400 V, three-phase voltage source inverter system using Sinusoidal Pulse Width Modulation (SPWM) control technique. Pulse Width Modulation (PWM) is an internal control technique for inverters. The Sinusoidal Pulse Width Modulation (SPWM) technique is the type of PWM used in this work. The aim is to reduce the harmonic produced by the inverter. Current standards require that total harmonic distortion (THD) be minimal. A three-phase SPWM signal is implemented in order to create an output voltage which is closer to a true sine wave and reduce harmonics. The development and model were implemented using MATLAB Simulink soft-ware and hardware parameters. The addition of a low pass filter circuit aids the achievement of smoother sine waveforms and a reduced THD value of 0.17%. The proposed concept has been validated through experimentally on a laboratory prototype by using DSP TMS320F28335 real-time digital control. The experimental outcomes emphasize the authenticity of the suggested technique in reducing harmonics, which can be promising to power quality improvement.